1995
DOI: 10.1152/jappl.1995.78.6.2100
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and systemic hemodynamics during exposure to 2 kPa CO2-300 kPa O2 in rats

Abstract: Cerebral blood flow (CBF), systemic hemodynamics, and arterial blood gases were measured during control conditions and during and after exposure to either 300 kPa O2 (group 1) or 300 kPa O2 with 2 kPa CO2 (group 2) in awake rats. The respiratory frequency fell with no change of arterial PCO2 (PaCO2) in group 1, but in group 2, respiratory frequency and PaCO2 increased linearly. The cardiac output (CO) and heart rate (HR) fell and systolic arterial pressure (SAP) rose independent of PACO2. O2 breathing caused C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Hyperoxia increases systemic vascular resistance, reduces cardiac output, and paradoxically reduces whole body O 2 consumption,44 reducing slightly the adenine nucleotide pool 45. Hyperbaric hyperoxia causes a decline in heart rate and cardiac output, whereas blood pressure increases, with depression of capillary blood flow 46. O 2 delivery is unchanged by hyperoxia at low hyperbaric levels or at eubaria,47 supporting a vascular, not a parenchymal effect of O 2 in explaining our findings.…”
Section: Discussionsupporting
confidence: 53%
“…Hyperoxia increases systemic vascular resistance, reduces cardiac output, and paradoxically reduces whole body O 2 consumption,44 reducing slightly the adenine nucleotide pool 45. Hyperbaric hyperoxia causes a decline in heart rate and cardiac output, whereas blood pressure increases, with depression of capillary blood flow 46. O 2 delivery is unchanged by hyperoxia at low hyperbaric levels or at eubaria,47 supporting a vascular, not a parenchymal effect of O 2 in explaining our findings.…”
Section: Discussionsupporting
confidence: 53%
“…Although the overall effect of HBO is to lower CBF, prior to the development of HBO-induced seizures, there is a significant increase in CBF [52, 53]. This increase has been causally linked to the development of seizures as vasodilation through exposure to CO 2 decreases seizure latency in HBO exposed animals [54]. Also, vasodilatory nitric oxide levels have been found to be increased by HBO [53], and inhibitors of nitric oxide synthase increase seizure latency and attenuate increases in CBF [53, 55].…”
Section: Mechanism Of Action Of Hbomentioning
confidence: 99%
“…However there is no information on the circulatory responses in dierent organs to a combined O 2 -CO 2 exposure, except for our recent demonstration of the increase in regional cerebral blood¯ows (Bergù and Tyssebotn 1995a). Theoretically, adding CO 2 to the hyperoxic breathing atmosphere might have unfavorable eects in addition to those eects caused by the O 2 itself, for example, in rats excess CO 2 potentiates the toxic eect of HBO, by reducing the latency to seizures (Kafka et al 1986;Bergù and Tyssebotn 1995a).…”
Section: Introductionmentioning
confidence: 95%
“…This work con®rms previous studies (Lambertsen 1978;Kafka et al 1986) that demonstrated a reduced O 2 tolerance in hypercapnic animals. The lowered seizure-threshold may be due to an increased production of O 2 radicals due to the high oxygen tension (Bergù and Tyssebotn 1995a) or altered cellular metabolic responses to changes in arterial pH and P a CO 2 . The present study supports the hypothesis that cerebral vasoconstriction during HBO exposure is a protective mechanism that delays the onset of O 2 induced convulsions (Donald 1947;Lambertsen 1978;Kafka et al 1986) in conscious animals and humans.…”
Section: Evaluation Of the Experimental Proceduresmentioning
confidence: 99%